Advanced computational methods for knowledge engineering : proceedings of the 5th International Conference on Computer Science, Applied Mathematics and Applications, ICCSAMA 2017 /: proceedings of the 5th International Conference on Computer Science, Applied Mathematics and Applications, ICCSAMA 2017. (2018) - Unknown
No abstract available